PENGARUH KARAKTER GEMAR MEMBACA SISWA TERHADAP MINAT BELAJAR PPKn Di SMP NEGERI 4 TAMBANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Febriani, Dian; Gimin, Gimin; Hambali, Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of the character likes to read students towards the learning interest of PPKn in the Mine 4 Middle School in Tambang District, Kampar Regency. As for the population, there are 322 students in class VIII and 64 students using a proportional random sampling technique. Data collection techniques used are through observation, questionnaires and documentation. In analyzing using simple linear regression analysis. The results of this study indicate that there are influential characters like reading students towards the learning interest of PPKn in the State Middle School 4 Tambang District of Kampar Regency. This is evidenced by a series of simple linear regression tests between X Variables and Y Variables, obtained Fcount (34.30) > Ftable (4.00) with Sig. (0.000) ˂ (0.05) thus Ho is rejected and Ha is accepted. The meaning is that the Influence of Characters Like Reading Students Against the Interest in Studying PPKn in SMP Negeri 4 Tambang, Tambang District, Kampar Regency is significant.Key Words: Characters likes to read, interest in learning PPKn